Impact of various additives and their combinations on the consolidation characteristics of clayey soil - Soheila Shojamoghadam; Arash Rajaee; Saeed Abrishami (Scientific Reports)
Abstract Improving highway bases is the most crucial step that enhances pavements’ performance and long-term durability. Lime and Portland cement are commonly used in soil stabilization endeavors. Nevertheless, the substantial carbon emissions associated with cement and lime manufacturing have led to a growing interest in researching environmentally friendly additives. Through standard proctor compaction tests and one-dimensional consolidation tests, this research investigates the consolidation behavior of fine-grained soil stabilized with various content of additives such as fly ash (FA), volcanic ash (VA), marble powder (MP), cement, and lime and their combination at different curing times (7, 14, 28, and 90 days). Furthermore, to evaluate the characteristics of materials, tests such as Atterberg limits, soil grain size distribution, X-ray fluorescence (XRF), scanning electron microscope (SEM), particle size analysis (PSA), and energy dispersive spectroscopy (EDS) have been performed on the selected materials. Various stabilizing agents have different effects on consolidation and compaction behavior, with maximum dry density (MDD) decreasing with higher additives content and optimum moisture content (OMC) values generally increasing, except for MP-stabilized samples. The results indicate that the addition of FA, VA, MP, cement, and lime results in compressibility reductions. By raising the proportion of FA, VA, and MP additives to 20% and extending the duration of curing to 90 days, the compression index (Cc) coefficients decreased by 63%, 42%, and 54%, while the swelling index (Cs) coefficients decreased by 89%, 90%, and 81%, respectively. Since the samples enhanced with cement and lime showed superior performance, this study explored substituting a proportion of the cement or lime with FA, VA, and MP, as well as the simultaneous effect of 2 additives. Substituting cement with MP produces better consolidation outcomes compared to VA and FA in cement-stabilized samples. Furthermore, replacing lime in VA-stabilized samples has shown significantly better results than using cement or MP instead.